Drawing Glasgow School of Art: the graphics of reconstruction. Issue 4 (23rd November 2018) - Rodger, Johnny
Abstract : The Glasgow School of Art has a long history of the cultivation of the art of drawing. Many types of drawing have been taught and practiced within the institution since its establishment in 1845. Mackintosh's Glasgow School of Art building, completed between 1897 and 1909, can be seen as one great outcome of that design-through-tradition. The building not only sheltered and thus enabled a further cultivation of the art of drawing, but became itself a model for the practices of that drawing tradition. There is a strong body of work, much of it by teachers and students of the Mackintosh School of Architecture, which has focussed on the building and explored through drawing the architectonic features and significance of the structure. This work has been useful as a teaching and critical aid but also as a contribution to the art and discipline of architecture. In the wake of the first 2014 fire, which destroyed part of the building, this body of work suddenly became of use as a design tool rather than simply an exploratory or critical tool, as the institution sought to reproduce exactly what had been lost. The most recent 2018 fire wreaked a destruction much more comprehensive across the whole building. Accordingly, we are forced to completely review the relationship of that drawing heritage to the building. That is to say, the building largely no longer exists, and the drawings take on a life of their own in a way not previously attached to them. The school may, however, be rebuilt, recreated 'as was' at some point in the future, potentially instigating yet another type of relationship between the existing drawing work and a new 'Mackintosh' building.